QUALITATIVE RESEARCH ON THE ROLE AND IMPACT OF MARKETING ACTIVITY FOR CREATING A HIGHER STANDARD OF LIFE - Oana Maria SECARĂ; Carmen ACATRINEI (Annals of the University of Oradea: Economic Science)
This paper aims to highlight the role of marketing and its influences on society's standard of living. Starting from the phrase "the role of marketing is to ensure a higher standard of living", it has been analyzed how marketing has an impact on society by: knowing the needs of customers and potential customers, ensuring a balance in the economic system, creating new jobs and facilitating the process of specialization and international trade. The role of marketing has therefore been analyzed from different perspectives, with concrete examples of real life being provided. The purpose established in order to carry out the qualitative research was identifying the attitudes of marketing specialists regarding the impact of marketing activity on the standard of living. At the same time, this paper contains the results of our conducted reaserch carried out by applying an interview to marketing specialists with the help of an interview guide.